Factor affects customer behavior during currency depreciation - Bakri, Mohammed Hariri; Dabas, Nurayati; Azman, Hartini (Penerbit Universiti Teknikal Malaysia Melaka, 2021)
Nowadays, Malaysia face on currency depreciation right now and many industries get negative impact from this current situation. This present study aims to study the most factor effect on customer buying behavior during currency depreciation in Johor Bahru and this factor include culture factor, personal factor, social factor and currency factor. First, several study about factor effect customer behavior, buying behavior and currency depreciation already obtain. In order to investigate the effects of currency depreciation on customer buying behavior in Johor Bahru, researcher selects the 384 customer as our sample framework. The data gathered were analyzed by using descriptive analysis. The finding shows that there is a significant relation between Culture Factor, Social Factor and Currency Factor (independent variable) and the Customer Buying Behavior (dependent variable). Researcher also recommends future researcher to focus one product to do a comparison of consumer buying behavior in different area of Malaysia like southern area of Malaysia and east coast Malaysia where Pahang, Terengganu, and Kelantan where there are culture difference.